A method for determining critical force and anaerobic impulse capacity in tethered swimming - Papoti, M.; Silva, A. S. R.; Vitório, R.; Araújo, G. G.; Santhiago, V.; Martins, L. E. B.; Cunha, A. S.; Gobatto, C. A. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
The critical power model has been used to measure aerobic and anaerobic capacity. The aerobic and anaerobic capacities measured in tethered swimming by the critical power model are named critical force (CritF) and anaerobic impulse capacity (AIC), respectively. The objective of this study was to determine whether CritF and AIC - estimated by tethered swimming - reflect the aerobic and anaerobic performance of swimmers. Methods: Twelve swimmers performed incremental test in tethered swimming until exhaustion to determine lactate threshold (LT), maximal oxygen uptake (VO2max) and force of swimming associated with the VO2max (iVO2max). The swimmers performed four exhaustive (tlim) exercise bouts (100, 110, 120 and 130% ) to compute the CritF and AIC (F vs. 1/tlim model); a 30- s all out tethered swimming bout to determine their anaerobic fitness (ANF); 100, 200, and 400-m time-trials to determine the swimming performance. Results: CritF (57.09 ± 11.77 N) did not differ from LT (53.96 ± 11.52 N, (P>0.05) but was significantly lower of iVO2max (71.02±8.36N). In addition, CritF presented significant correlation with LT (r=0.76; P<0.05) and (r=0.74; P<0.05). On the other hand, AIC (286.19 ± 54.91 N.s) and ANF (116.10 ± 13.66 N) were significantly correlated. In addition, CritF and AIC presented significant correlations with all time-trials. Discussion: In the present investigation, CritF did not differ from LT, but presented significant correlation with the same variable. Perandini et al. (2007) found significant correlations between CritF values determined from different mathematical models and CV (r=0.89 to 0.91), concluding that CritF could be used as an indicator of aerobic capacity. Another interesting finding of our investigation was the significant correlation between AIC and ANF (r=0.81; P=0.001), and between AIC and maximal free swimming performances. These significant correlations contradicted results generally found in associations between AIC and ANF and between AIC and free swimming performances (Soares et al. 2003, Toussaint et al. 1998, Dekerle et al. 2001). In summary, this study demonstrate that CritF and AIC can be used to evaluate LT and ANF and to predict 100, 200, and 400-m free swimming.